HARMONI NILAI PESANTREN DAN BAHASA JEPANG: ANALISIS KEBUTUHAN PENGEMBANGAN MATERI PEMBELAJARAN DI MADRASAH ALIYAH - Laili Nurul; Miftakhul Ilmi Suwignya Putra; Ulwiyah Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
This study aims to examine the harmony of pesantren values with the Japanese language in terms of analyzing the needs for developing learning materials at Madrasah Aliyah. In the context of globalization, learning foreign languages, including Japanese, is one of the important aspects to improve the competence of graduates in international competition. However, the integration of pesantren values, rooted in Islamic education, into Japanese language learning has not been widely explored either in the scope of general education or in the local pesantren environment. This study uses a descriptive qualitative approach with literature study methods and interviews with teachers and policy makers at Madrasah Aliyah, especially at MAN 2 Jombang which is located in the Darul 'Ulum Jombang pesantren environment. Based on this initial observation study, it was found that pesantren values in the pesantren-based education complex, such as noble morals, discipline, honesty, cooperation, and others are in line with Japanese cultural principles such as hard work and mutual respect. The integration of these two aspects has the potential to create contextualized and character value-laden Japanese learning materials. The findings of this study provide a foothold for the development of value-based learning modules, which not only improve linguistic language skills, but also shape learners' characters in accordance with pesantren values